The Effect of Special Weight Exercises Using Auditory Apparatus According to Kinematic Indicators For Developing Auditory Response and Accuracy of Spiking in Volleyball - Yasir, Alaa Muhsun; Sikhe, Husein Sabhan (International Journal of Psychosocial Rehabilitation, 2020)
The research aimed at designing weight exercises using auditory apparatus according to kinematic indicators for developing auditory response and the accuracy of spiking in volleyball as well as to identify the effect of these exercises on the developing auditory response and the accuracy of spiking in volleyball players. The subjects of the research were (12) volleyball players from the national center for gifted in volleyball/ Ministry of Youth and Sports in Baghdad. Two setters as well as the libero were excluded making total of (9) players as research subjects. The researchers used special weight exercises using auditory apparatus according to some kinematic indicators for developing auditory response and spiking accuracy in volleyball players. Kinovea was used for motor analyses to conclude the kinematical variables of spiking in volleyball. Spiking accuracy test was conducted on volleyball players using auditory apparatus. The results showed a great development in auditory response and spiking accuracy in the subjects understudy as well as there was an improvement in some kinematical variables due to these exercises using the auditory apparatus according to kinematical variables.